Duties of Physical Education, Sports, and Health Teachers in School Health Effort - Sahabuddin, Sahabuddin (Universitas Majalengka, 2024)
This research is descriptive research using the survey method. The subjects of the research used were 8 elementary school teachers in Soreang District, Pare-Pare City. The instrument used was a questionnaire and to analyze the data, quantitative descriptive statistics were used with percentages. This study aims to determine how high the duties of physical education and health teachers are in implementing the School Health Effort program in elementary schools in Soreang District, Pare-Pare City. The results showed that the duties of physical education, sports and health teachers in implementing the School Health Effort in elementary schools in Soreang District, Pare-Pare City were mostly in the frequent category with a percentage of 41.8%, in the always category 39.3%, in the rarely category 16.18%, in the never category 2.1%.